PLCB1 epileptic encephalopathies; Review and expansion of the phenotypic spectrum. (May 2016) - Schoonjans, An-Sofie; Meuwissen, Marije; Reyniers, Edwin; Kooy, Frank; Ceulemans, Berten
Abstract: Background: Biallelic loss-of-function mutations of phospholipase C-β1 ( PLCB1 ) have been described in three children with an early onset epileptic encephalopathy (EE). In two of them a homozygous deletion of the promotor and first three coding exons was found. The third patient had an almost identical heterozygous deletion in combination with a heterozygous splice site variant. All patients had intractable epilepsy and a severe developmental delay. Methods and results: We present the case of a boy with an infantile EE starting at the age of four months with a fever induced status epilepticus, modified hypsarrhythmia and developmental regression. The epilepsy was reasonably controlled with corticoids and valproate whereupon generalized tonic-clonic seizures appeared only each 3–4 months. However, only a slow developmental progress was seen hereafter, resulting in a severe intellectual disability with absent speech, motor delay and autistic features. We identified a novel homozygous partial deletion of PLCB1, affecting exons 7–9. Conclusions: This report emphasizes the role of PLCB1 haploinsufficiency in severe EE. We demonstrate a phenotypic variability in patients with a PLCB1 -associated EE. In addition, our findings underscore the importance of microarray analysis in all patients with an EE of unknown etiology. Highlights: Biallelic loss-of-function mutations of PLCB1 are associated with early onset EE. Presentation and outcome of a PLCB1 -associated EE can be variable. Micro-array remains essential in cases with an unexplained EE.